2017
DOI: 10.3389/fpls.2017.00143
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Single-Nucleotide Polymorphisms in CMS and Restorer Lines Discovered by Genotyping Using Sequencing and Association with Marker-Combining Ability for 12 Yield-Related Traits in Oryza sativa L. subsp. Japonica

Abstract: Heterosis or hybrid vigor is closely related with general combing ability (GCA) of parents and special combining ability (SCA) of combinations. The evaluation of GCA and SCA facilitate selection of parents and combinations in heterosis breeding. In order to improve combining ability (CA) by molecular marker assist selection, it is necessary to identify marker loci associated with the CA. To identify the single nucleotide polymorphisms (SNP) loci associated with CA in the parental genomes of japonica rice, geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 106 publications
1
9
0
Order By: Relevance
“…In this study, the genomic positions of associated SNPLDBs were compared with the reported genomic positions of GCA. The associated SNPLDBs of GCA of PH and ST on chromosomes 6, 7 and 11 were close to the chromosomal regions of previously identified alleles of PH and ST with combining abilities (Zaid et al 2017). Additionally, most of the associated SNPLDBs were located in adjacent intervals of the same chromosome that used a diverse set of ILs (Xiang et al 2016).…”
Section: Discussionsupporting
confidence: 77%
“…In this study, the genomic positions of associated SNPLDBs were compared with the reported genomic positions of GCA. The associated SNPLDBs of GCA of PH and ST on chromosomes 6, 7 and 11 were close to the chromosomal regions of previously identified alleles of PH and ST with combining abilities (Zaid et al 2017). Additionally, most of the associated SNPLDBs were located in adjacent intervals of the same chromosome that used a diverse set of ILs (Xiang et al 2016).…”
Section: Discussionsupporting
confidence: 77%
“…The SNP data of this study were obtained from Zaid et al [39], and are available at NCBI under accession number SRR7250921. The missing genotypes in the sequence data were precisely predict through the fas-tPHASE software [35].…”
Section: Amylose Contentmentioning
confidence: 99%
“…Associated loci residing on chromosomes 2, 5, 7, 9, and 11 that recorded maximum positive values for the CA of traits were identified. It was concluded that the strategy to improve the heterosis of hybrid japonica rice involved pyramiding favorable SNP loci of CA and eliminating the unfavorable loci from parental genomes (Zaid et al 2017).…”
Section: Progress In Genetic Studies On Traits Related To Heterosis Utilization Yield and Hybrid Vigormentioning
confidence: 99%